2020
DOI: 10.1186/s12935-020-01557-5
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0000285 regulates proliferation, migration, invasion and apoptosis of osteosarcoma by miR-409-3p/IGFBP3 axis

Abstract: Background Circular RNAs (circRNAs) are important regulators in the pathogenesis of diseases and affects the occurrence and development of diseases. However, the role of circRNAs in osteosarcoma (OS) has not been fully elucidated. Methods The expression of circ_0000285, miR-409-3p and insulin-like growth factor binding protein 3 (IGFBP3) was detected using quantitative real-time PCR (qRT-PCR). The protein level of IGFBP3 was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 41 publications
1
36
0
Order By: Relevance
“…For example, Zhang et al ( 28 ) confirmed that circ_0067934 depletion accelerates cell apoptosis and represses cell proliferation, migration and invasion in thyroid cancer by sponging miR-1304 and regulating C-X-CR motif chemokine receptor 1 expression. hsa_circ_0000285 is a novel circRNA that is dysregulated in various cancers and disease types, including osteosarcoma ( 29 ), diabetic nephropathy ( 30 ) and laryngocarcinoma ( 31 ). However, the specific role and molecular mechanism of circ_0000285 in thyroid cancer have not yet been fully investigated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhang et al ( 28 ) confirmed that circ_0067934 depletion accelerates cell apoptosis and represses cell proliferation, migration and invasion in thyroid cancer by sponging miR-1304 and regulating C-X-CR motif chemokine receptor 1 expression. hsa_circ_0000285 is a novel circRNA that is dysregulated in various cancers and disease types, including osteosarcoma ( 29 ), diabetic nephropathy ( 30 ) and laryngocarcinoma ( 31 ). However, the specific role and molecular mechanism of circ_0000285 in thyroid cancer have not yet been fully investigated.…”
Section: Discussionmentioning
confidence: 99%
“…After being isolated from LN229 and T98G cells, total RNA was incubated with RNase R or the mock treatment for 30 min (37°C). Then, the expression of circ_0001367 and GAPDH was determined by qRT-PCR ( 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…Actinomycin D (2 mg/ml, APExBIO, USA) was added to culture medium to culture LN229 and T98G cells for 24 h. Next, the cells were harvested, and their expression of circ_0001367 and GAPDH was determined by qRT-PCR ( 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…Most patients with OS will eventually die of lung metastases [4] . Research results have proven that the occurrence and evolution of OS are closely related to gene mutations and expression levels [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%